The TAB book of arduino projects : 36 things to make with shields and protoshields - Monk, Simon (New York, N.Y. : McGraw-Hill Education LLC., 2015)
In this easy-to-follow book, electronics guru Simon Monk show you how to create a wide variety of fun and functional gadgets with the Arduino Uno and Leonardo boards. Filled with step-by-step instructions and detailed illustrations, The TAB Book of Arduino Projects: 36 Things to Make with Shields and Proto Shields provides a cost estimate, difficulty level, and list of required components for each project. You'll learn how to design custom circuits with Proto Shields and solder parts to the prototyping area to build professional-quality devices. Catapult your Arduino skills to the next level with this hands-on guide.
15. Spectrum Display -- Parts -- Construction -- Software -- Using the Project -- Summary -- D. PART FOUR: Internet -- 16. E-Mail Notifier -- Parts -- Construction -- Software -- Using the Project -- Summary -- 17. Weather Data Feed -- Parts -- Construction -- Software -- Using the Project -- Summary -- 18. Network-Controlled Switch -- Parts -- Construction -- Software -- Using the Project -- Summary -- 19. Network Temperature and Humidity Sensor -- Parts -- Construction -- Software -- Using the Project -- Summary -- 20. Pingometer -- Parts -- Construction -- Software -- Using the Project -- Summary -- E. PART FIVE: Clocks -- 21. LED Matrix Clock -- Parts -- Protoshield Layout -- Construction -- Software -- Summary -- 22. Binary Clock -- Binary -- Parts -- Protoshield Layout -- Construction -- Software -- Summary -- 23. Seven-Segment LED Clock -- Parts -- Protoshield Layout -- Construction -- Software -- Summary -- 24. Hacked Analog Clock -- Parts -- Construction -- Software -- Using the Project -- Summary -- 25. World Clock -- Parts -- Construction -- Software -- Using the Project -- Summary -- F. PART SIX: Novelty -- 26. Larson Scanner -- Parts -- Wiring Diagram -- Construction -- Software -- Summary -- 27. Conway's Game of Life -- Parts -- Construction -- Software -- Summary -- 28. Singing Plant -- Parts -- Construction -- Software -- Summary -- 29. Ultrasonic Range Finder -- Parts -- Construction -- Software -- Summary -- 30. GPS -- Parts -- Construction -- Software -- Using the Project -- Summary -- 31. Methane Detector -- Parts -- Construction -- Software -- Using the Project -- Summary -- G. PART SEVEN: Home -- 32. Light-Level Logger -- Parts -- Construction -- Software -- Using the Project -- Summary -- 33. Temperature and Light Logger -- Parts -- Construction -- Software -- Using the Project -- Summary -- 34. Timer-Controlled Lamp -- Parts -- Construction -- Software -- Using the Project -- Summary -- 35. Autoranging Capacitance Meter -- Parts -- Construction -- Software -- Using the Project -- Summary -- 36. Geiger Counter -- Parts -- Construction -- Software -- Using the Project -- Summary -- H. APPENDIX: Component Buying Guide -- Arduino -- Hardware -- Modules and Sheilds -- Resistors -- Semiconductors -- Other Components.
Includes bibliographical references and indexes.
Cover image and table of contents, viewed on February 20, 2015.
English.
Keywords: Arduino (Programmable controller); Electronics -- Data processing; Arduino (Automate programmable); Électronique -- Informatique; Arduino (Programmable controller); Electronics -- Data processing